2019
DOI: 10.1002/lol2.10105
|View full text |Cite
|
Sign up to set email alerts
|

Particulate inorganic to organic carbon production as a predictor for coccolithophorid sensitivity to ongoing ocean acidification

Abstract: Ocean acidification (OA) can induce shifts in plankton community composition, with coccolithophores being mostly negatively impacted. This is likely to change particulate inorganic and organic carbon (PIC and POC, respectively) production, with impacts on the biological carbon pump. Hence, assessing and, most importantly, understanding species‐specific sensitivities of coccolithophores is paramount. In a multispecies comparison, spanning more than two orders of magnitude in terms of POC and PIC production rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
0
20
0
2
Order By: Relevance
“…Across the modern representatives of the Helicosphaera genus, coccolith dimensions and cell size are correlated. For example, the smallest coccolith and coccosphere sizes are found in H. pavimentum (coccolith 4-6 µm, coccosphere 9-16 µm) and in H. hyalina (coccolith 5-8 µm, coccosphere 11-16 µm), whereas the largest coccolith and coccosphere sizes are found in H. carteri (coccolith 7-12 µm, coccosphere 15-25 µm) and H. wallichii (coccolith 7-12 µm, coccosphere 19-27 µm; http://www.mikrotax.org/Nannotax3/index.php?dir= Coccolithophores, last access: 4 May 2020; Geisen et al, 2004). It can therefore be argued with confidence that these traits followed the same principle in extinct fossil representatives, meaning that H. sellii had smaller coccolith and cell size than H. carteri, while H. granulata had the largest cell size of the three species.…”
Section: Are Coccolith Dimensions a Proxy For Cell Physiology?mentioning
confidence: 99%
See 2 more Smart Citations
“…Across the modern representatives of the Helicosphaera genus, coccolith dimensions and cell size are correlated. For example, the smallest coccolith and coccosphere sizes are found in H. pavimentum (coccolith 4-6 µm, coccosphere 9-16 µm) and in H. hyalina (coccolith 5-8 µm, coccosphere 11-16 µm), whereas the largest coccolith and coccosphere sizes are found in H. carteri (coccolith 7-12 µm, coccosphere 15-25 µm) and H. wallichii (coccolith 7-12 µm, coccosphere 19-27 µm; http://www.mikrotax.org/Nannotax3/index.php?dir= Coccolithophores, last access: 4 May 2020; Geisen et al, 2004). It can therefore be argued with confidence that these traits followed the same principle in extinct fossil representatives, meaning that H. sellii had smaller coccolith and cell size than H. carteri, while H. granulata had the largest cell size of the three species.…”
Section: Are Coccolith Dimensions a Proxy For Cell Physiology?mentioning
confidence: 99%
“…One possible explanation for different adaptive strategies can be related to the distinction between obligate calcifiers, including Coccolithus and Helicosphaera, and nonobligate calcifiers, such as Emiliania huxleyi (Durak et al, 2016;Walker et al, 2018). The phenotypic plasticity in obligate calcifiers could be more restricted when it comes to morphological innovation and biogeochemical output compared to nonobligate calcifiers, who can regulate their calcification rates (and thus PIC : POC ratio) to zero and overcome carbon limitation or other environmental stressors such as ocean acidification (Gafar et al, 2019). Obligate calcifiers, such as Coccolithus, Calcidiscus and Helicosphaera, combined were relatively more abundant than reticulofenestrids until ∼ 7 Ma when their fluxes decreased significantly at both sites (Fig.…”
Section: Biogeochemical Implications Of Phenotypic Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic plasticity in obligate calcifiers could be more restricted when it comes to morphological innovation and biogeochemical performance compared to non-obligate calcifiers, who can regulate their calcification rates (and thus PIC:POC ratio) to zero and overcome carbon limitation or other environmental stressors such as ocean acidification (Gafar et al, 2019).…”
Section: Biogeochemical Implications Of Phenotypic Evolutionmentioning
confidence: 99%
“…Earlier experimental studies have found a range of strain-specific physiological traits in H. carteri, likely related to local eco-physiological adaptation (Šupraha et al, 2015). In addition, this species is considered highly susceptible to ocean acidification due to its heavily calcified coccoliths and high PIC:POC ratio (Gafar et al, 2019). Finally, both modern and fossil Helicosphaera morphospecies are well-defined and identifiable under a light microscope, which allows for long-term tracking of speciation events, community dynamics and phenotypic evolution at the morphospecies-level.…”
Section: Introductionmentioning
confidence: 99%